2016
DOI: 10.1111/jdv.13864
|View full text |Cite
|
Sign up to set email alerts
|

Topical cetirizine and oral vitamin D: a valid treatment for hypotrichosis caused by ectodermal dysplasia

Abstract: We propose a combination of topical cetirizine and oral vitamin D as a rational treatment of choice in congenital hypotrichosis caused by ectodermal dysplasia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 21 publications
0
6
0
1
Order By: Relevance
“…The vellus hair replacement by terminal hair was noticed in this report. Furthermore, after 6 months of treatment, the density of hair on the scalp increased in all patients from clinical and trichoscopic points of view (8). Also, recently published a research article in the journal of cosmetic dermatology which indicated a potential role of cetirizine 1% in treating AGA (18).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The vellus hair replacement by terminal hair was noticed in this report. Furthermore, after 6 months of treatment, the density of hair on the scalp increased in all patients from clinical and trichoscopic points of view (8). Also, recently published a research article in the journal of cosmetic dermatology which indicated a potential role of cetirizine 1% in treating AGA (18).…”
Section: Discussionmentioning
confidence: 93%
“…Cetirizine hydrochloride belongs to a family of medicines called antihistamine which has varied medical uses and is commonly used to relieve allergy symptoms such as watery eyes, runny nose, sneezing, hives, and itching. In addition, it has been demonstrated that cetirizine inhibits release of prostaglandin D2 and stimulates the release of prostaglandin E2 (6,8). Furthermore, it has antiinflammatory properties which can be useful because perifollicular micro-inflammation of the scalp is one of deteriorating factors in AGA (9,1).…”
Section: Introductionmentioning
confidence: 99%
“…), and black dots (B.D). Table (2) Photographic examples of clinical and dermoscopic responses in patients are demonstrated in Figures 3-4.…”
Section: Resultsmentioning
confidence: 99%
“…Since the increase in hair density was significant in both groups, it will be hard to know if cetirizine had a role in it. However, a short report by Rossi et al in patients with congenital hypotrichosis caused by ectodermal dysplasia [ 24 ] and a case report of a 70-year-old woman with chemotherapy-induced alopecia [ 25 ] showed positive effect of topical cetirizine on hair density.…”
Section: Discussionmentioning
confidence: 99%